Creativity and Innovation in Philosophy Learning: A Literature Study - Otto Mart Andreas; Danny Philipe Bukidz (Indonesian Journal of Advanced Research, 2023)
This research is a literature study that aims to dig up information related to creativity and innovation in teaching philosophy. Philosophy is a scientific discipline that requires critical and creative thinking, but teaching philosophy often feels monotonous and boring for some students. Therefore, this research wants to find various creative and innovative strategies that can be applied in teaching philosophy to make it more attractive and motivating for students. The method used in this research is literature study by collecting and analyzing various journal articles, books, and information sources related to creativity and innovation in teaching philosophy. The results of this study are expected to contribute to the development of more creative and innovative philosophy teaching strategies and to motivate students to learn philosophy better.